2019
DOI: 10.3389/fpls.2019.01354
|View full text |Cite
|
Sign up to set email alerts
|

Australian Wild Rice Populations: A Key Resource for Global Food Security

Abstract: Rice is one of the most important food crops contributing to the diet of large numbers of people especially in Asia. Rice (Oryza sativa) was domesticated in Asia many thousands of years ago and more recently independently in Africa. Wild rice populations are found around the tropical world. The extensive production of rice in many areas has displaced the wild populations that were the basis of the original domestications by humans. Recent research, reviewed here, has identified wild rice species in northern Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Efforts are ongoing to identify high salttolerant genetic resources for the improvement of salt tolerance in rice [6,42]. Wild rice O. australiensis is considered a potential candidate due to its ability to tolerate many abiotic and biotic stresses [39,[43][44][45][46]. However, tolerance to high concentrations of salt, a criterion for being a salt-tolerant trait donor, has not been studied in this wild rice species.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts are ongoing to identify high salttolerant genetic resources for the improvement of salt tolerance in rice [6,42]. Wild rice O. australiensis is considered a potential candidate due to its ability to tolerate many abiotic and biotic stresses [39,[43][44][45][46]. However, tolerance to high concentrations of salt, a criterion for being a salt-tolerant trait donor, has not been studied in this wild rice species.…”
Section: Discussionmentioning
confidence: 99%
“…The CWRs have a high genetic diversity and can contribute to new genetic diversity for agricultural sustainability [85]. For instance, previous research has indicated that several recently discovered wild rice species in northern Australia have unique alleles for distinct critical traits, which could improve the ability of cultivated rice to withstand climate change [86]. The ability of the same species to display distinct features under different environmental situations is referred to as phenotypic plasticity.…”
Section: Implications For the Origin And Adaptation Of O Nivaramentioning
confidence: 99%
“…For example, Henry (2019) highlighted several recently identified wild rice species with most divergent genotypes in northern Australia containing novel alleles for various important traits, which could enhance the capacity of cultivated rice to tolerate climate change. During the past decade, dozens of review/ perspectives have been published to highlight the potential and importance of crop wild relatives in meeting global challenges (e.g., Brozynska et al, 2016;Zhang et al, 2017Zhang et al, , 2019Mammadov et al, 2018;Fernie & Yan, 2019;Henry, 2019). Nevertheless, few climate-adaptive casual genes identified in CWR have been applied to the development of crops that can withstand climate change.…”
Section: Research Gapsmentioning
confidence: 99%